Transforming attitudes to death in the Information Society - Марійко, С.В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2012)
The article tries to analyze contemporary forms of thinking and "obzhivanie" kinechnosti being transformation of views on this phenomenon, considered images of death in the information society.